RESEARCHER PERCEPTION ON E-RESOURCES AT BABASAHEB BHIMRAO AMBEDKAR UNIVERSITY (A CENTRAL UNIVERSITY), LUCKNOW: A STUDY - Ashwani Kumar; Dr. M.P. Singh (Researchers World - International Refereed Social Sciences Journal, 2021)
This study examines the perception research scholars on e-resources at BBAU, Lucknow including preferred information sources and methods of electronic information access. The study describes in brief, the e-resources and their types, etc. The objectives, scope, research methodology of the study are clearly expanded. The data analysis and interpretation are given on total number of responses, purposes of seeking information utilizing on e-resources, way to use of e-resources etc. by science research scholars.